Shared Decision-Making Tools Help Patients Make Quicker Orthopedic Treatment Decisions - Parry, Nicola (MD Conference Express, 2014)
This article, presented data from a randomized controlled trial, demonstrating that more patients made informed treatment decisions during their first appointment with an orthopedic surgeon if shared decision-making (interventions were used [Bozic KJ et al. J Bone Joint Surg Am 2013].